Vital signs : perspectives on the health of American campaigning - Dulio, David A.; Nelson, Candice J., 1949- (Washington, D.C. : Brookings Institution Press, 2005)
"Through analysis of the 2004 presidential campaigns of George W. Bush and John F. Kerry, explores the strengths and weaknesses of the current U.S. campaign system and possible approaches to improving campaign conduct"--Provided by publisher
A tale of two campaigns? -- Who's in charge? Candidates, consultants, and political parties -- Where do we stand? A comparative view among the actors -- Money, elections, and the impact of reform -- Ethics and the health of American campaigning -- The health of U.S. campaigning after the 2004 election.
Includes bibliographical references (pages 181-214) and index.
Print version record.
English.
JSTOR
Keywords: Presidents -- United States -- Election -- 2004.; United States -- Politics and government -- 2001-; Political campaigns -- United States -- Case studies; United States -- Politics and government -- 2001-2009.; États-Unis -- Politique et gouvernement -- 2001-2009.; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Political Process -- Elections; Political campaigns; Politics and government; Presidents -- Election; United States; Since 2001; Electronic books; Case studies